Investigating assumptions in motivational interviewing among general practitioners: a qualitative study - Paul Aujoulat; Amélie Manac’h; Catherine Le Reste; Delphine Le Goff; Jean Yves Le Reste; Marie Barais (BMC Primary Care)
Abstract Background Unhealthy behaviours contributing to cardiovascular issues, diabetes, strokes, and cancer, pose significant health risks. General practitioners (GPs) are pivotal in guiding behaviour change, with Motivational Interviewing (MI) showing promise. MI, developed by William Miller and Stephen Rollnick, aims to enhance motivation for change. Despite its efficacy in areas like smoking cessation and weight loss, its uptake among French GPs remains uncertain. Methods This qualitative study was to explore GPs’ understanding of MI, its perceived benefits and the obstacles to its implementation in western Brittany (Finistère). Semi-structured interviews, conducted by two female trainees, explored MI knowledge, benefits, and barriers with a thematic analysis. Results Between November 2020 and May 2021, 11 semi-structured interviews were conducted with GPs. Participants had a limited understanding of MI, often confusing it with persuasion. MI was seen as a patient-centered tool fostering behavioural change, with reported benefits in cancer screening, chronic disease management, and vaccination. However, barriers such as time constraints, limited training availability, and systemic issues hinder its adoption. Participants emphasized MI’s utility for challenging cases but noted it was unnecessary for engaged patients. MI could also enhance doctor-patient relationships and physician satisfaction. Overcoming barriers requires addressing logistical issues, integrating MI into training, and promoting its long-term efficiency to improve healthcare outcomes. Conclusion This study highlighted GPs’ limited knowledge of MI but recognized its value in promoting patient-centered care and behaviour change. GPs identified its potential in areas like cancer screening, chronic disease management, and vaccine hesitancy while noting barriers such as time constraints and insufficient training. Addressing these challenges through better integration into training and practice could enhance patient outcomes and provider satisfaction. Focused efforts are needed to translate MI’s potential into routine clinical use.